Front Cover: Base‐Promoted Formation of an Annelated Pyrrolo‐1, 4‐oxazine Ensemble from 1H‐pyrrol‐2‐ylmethanol and Propargyl Chloride: A Theoretical and Experimental Study (ChemPlusChem 1/2020). Issue 1 (12th November 2019) - Vitkovskaya, Nadezhda M.; Bobkov, Alexander S.; Kuznetsova, Svetlana V.; Shcherbakova, Victoriya S.; Ivanov, Andrey V.
Abstract : The front cover shows that three different pyrrole derivatives can be obtained from the same starting reagents. The reaction is easily controlled by 1) the ratio of the starting reagents, 2) the amount of alkali, and 3) the degree of dilution. This process can be compared with playing the balalaika (a Russian folk instrument), where, by using just three strings, it is possible to produce beautiful melodies from the same notes. The three strings are associated with the three parameters, and the notes are the starting reagents. The sheets with quantum‐chemical calculations symbolize that the experimental work is based on theoretical investigations. More details are given in the Full Paper by N. M. Vitkovskaya and co‐workers on page 88 in Issue 1, 2020 (DOI: 10.1002/cplu.201900407 ).